Historis Konsep Prapengetahuan Allah dan Hubungannya dengan Predestinasi (Dari Abad Ke 1-10) - Ziduhu Laia, Harman (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2023)
The doctrine of God's foreknowledge and its relationship to predestination is one of the most challenging puzzles in theology to solve. This doctrine can only be understood as God reveals it in the Bible, and there are also various interpretations. The purpose of this study is to explain the history of this doctrine and its relation to God's predestination, which traces its history from the first to the tenth century. This research employs qualitative research methods by studying literature or the writings of church fathers from the first to the tenth century. The results show that there are two kinds of opinions about the concept of God's foreknowledge and its relation to predestination.